Synthetic utilities of the enamides for the synthesis of some alkaloids - Vanida Bhavakul (Mahidol University. Mahidol University Library and Knowledge Center, 2023)
Chapter I The reaction of various enamide derivatives with thallium (III) nitrate was investigated. Three different pathways were found to involve in such a reaction depaending on the structural feature of the enamide intermediates. In the case of enamides derived from N-acylation of the simple l-alkyl-3,4-dihydroisoquinolines, the rearrangement of the isoquinoline nucleus to the benzazepine derivative was observed. This finding of the crucial ring enlargement made the synthesis of the useful benzazepine derivatives more accessible. However, in the case of the enamides derived from the more complex l-benzyl and l-substituted benzyl-3,4- dihydroisoquinolines and the nitrogen atom substitured with alkoxycarbonyl groups or phenoxycarbonyl grous, the corresponding oxazolidone derivatives were the products of the reaction. The synthetic utility of the derived oxazolidone was briefly investigated. Moreover, in the third type of enamides dervied from l-benzyl and l-substituted benzyl-3,4-dihydroisquinoline with the nitrogen atom substituted with aroyl groups, the oxazolines were obtained. The mechanistic details of the above reactions were also discussed. Thermal rearrangement of various enamides was also invertigated. It was found that 1,3-acyl shift from the nitrogen atom to the carbon atom to give the vinylogous amide was observed upon heating of the enamide intermediates. The above finding proved that the thermal of the enamide is a viable process in contrast with the previously accepted view. Three approaches for the synthesis of isoindoloisoquinoline alkaloids were developed. The analysis of the syntheses of these alkaloids in term of bond formation was discussed. In the first approach, carbon-carbon bond formation ortho tothe side chain was effected followed by carbon-nitrogen bondformation. Final electrophilic aromatic substitutioncompleted the final carbon-carbon bond formation. In thesecond approach, the (aromatic) carbon-carbon bond was formedfirst which was then followed by the formation of carbon-carbonbond and carbonnitrogen bond respectively. Moreover, in the thirdapproach the isoquinoline ring was formed first, however unlikethe first two approaches, the formation of the isoquinoline ringis intermolecular reaction rather than the intramolecularreaction, the reaction was completed by the intramolecular lactambond formation.